Impact of soaring food price in Ethiopia: Does location matter? - Ulimwengu, John M.; Workneh, Sindu; Paulos, Zelekawork (International Food Policy Research Institute, 2009)
Previous studies implicitly assume uniform price-effects across regions or provinces within countries. They also do not address the issue of integration between the world food market and local markets. Instead, they assume a complete transmission of changes in world food prices to local food prices. In this paper, we first establish evidence of regional price heterogeneity across Ethiopia. We also applied the Johansen test for market integration over 95 local maize markets and found that none of the Ethiopian regional markets for maize is integrated to the world market. However, there is significant short-term price effects between the world maize market and some Ethiopian regional markets. Using the Almost Ideal Demand System, we estimate loss in household consumption and calorie intake as induced by food price increases. The results suggest a great deal of heterogeneity across regions as well as between rural and urban areas. Studies that fail to account for the characteristics of household demand across locations are more likely to induce misleading policy recommendations.